2023
DOI: 10.1021/acs.macromol.2c02318
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Polymerization-Induced Self-Assembly of Amphiphilic Copolymers

Abstract: The ability to have precise control over the designed structure and properties of molecular self-assemblies is critical for tailoring the quality and efficacy of their functionality, yet the underlying mechanisms governing the evolution from molecules into self-assembled structures are not fully resolved. Here, we employed the graphene liquid cell (GLC) transmission electron microscopy (TEM) approach to observe nucleation and evolution of individual nanoscale micelles during polymerization-induced self-assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…This pointed towards the potential electron beam-induced radical generation from poly GMA-CTA, which initiates HPMA monomer polymerization within a water medium. 36 Diverse systems were investigated using graphene liquid cells, offering comprehensive insights from fabrication to successful sample identification, enabling precise examination of various materials and processes 37 Lastly, leveraging liquid-phase TEM and a U-Net neural network, Chen et al demonstrated real-time imaging of colloidal nanoparticle systems, uncovering otherwise inaccessible nanoscale properties including anisotropic interactions, etching profiles, and kinetic assembly dynamics. 38…”
Section: Introductionmentioning
confidence: 99%
“…This pointed towards the potential electron beam-induced radical generation from poly GMA-CTA, which initiates HPMA monomer polymerization within a water medium. 36 Diverse systems were investigated using graphene liquid cells, offering comprehensive insights from fabrication to successful sample identification, enabling precise examination of various materials and processes 37 Lastly, leveraging liquid-phase TEM and a U-Net neural network, Chen et al demonstrated real-time imaging of colloidal nanoparticle systems, uncovering otherwise inaccessible nanoscale properties including anisotropic interactions, etching profiles, and kinetic assembly dynamics. 38…”
Section: Introductionmentioning
confidence: 99%